Pediatric obesity is associated with an altered gut microbiota and discordant shifts in Firmicutes populations. (22nd August 2016) - Riva, Alessandra; Borgo, Francesca; Lassandro, Carlotta; Verduci, Elvira; Morace, Giulia; Borghi, Elisa; Berry, David
Summary: An altered gut microbiota has been linked to obesity in adulthood, although little is known about childhood obesity. The aim of this study was to characterize the composition of the gut microbiota in obese ( n  = 42) and normal‐weight ( n  = 36) children aged 6 to 16. Using 16S rRNA gene‐targeted sequencing, we evaluated taxa with differential abundance according to age‐ and sex‐normalized body mass index (BMI z ‐score). Obesity was associated with an altered gut microbiota characterized by elevated levels of Firmicutes and depleted levels of Bacteroidetes . Correlation network analysis revealed that the gut microbiota of obese children also had increased correlation density and clustering of operational taxonomic units (OTUs). Members of the Bacteroidetes were generally better predictors of BMI z ‐score and obesity than Firmicutes, which was likely due to discordant responses of Firmicutes OTUs. In accordance with these observations, the main metabolites produced by gut bacteria, short chain fatty acids (SCFAs), were higher in obese children, suggesting elevated substrate utilisation. Multiple taxa were correlated with SCFA levels, reinforcing the tight link between the microbiota, SCFAs and obesity. Our results suggest that gut microbiota dysbiosis and elevated fermentation activity may be involved in the etiology of childhood obesity.